Full neurological recovery following tricyclic overdose associated with absent brainstem reflexes. (November 2018) - Webster, Deborah; Datar, Priya; Waddy, Sam
We report the case of an 18-year-old gentleman who presented to the emergency department following a large overdose of amitriptyline. He was comatose on admission but his neurology further deteriorated to global loss of brainstem reflexes. He made a full but slow neurological recovery. First signs of improving neurology were seen on day 3 of admission; he was extubated on day 6 and discharged home on day 9. There is limited recent literature to help guide prognostication in this group of patients.